Barrier for Implementation of Improved Cook Stove Program in Nepal - Bhattarai, Nawraj; Risal, Sunil (Journal of the Institute of Engineering, 2009)
More than 85% of total population lives in rural part of Nepal. Traditionally, they are mostly using biomass based cooking stove for cooking purpose. To substitute those traditionally using cooking stoves, many Improved Cooking Stoves (ICS) programs are implemented and now more than three hundred thousand improved cooking stoves are already installed in rural households across the country. To accelerate the installation of such stoves more commonly in coming days, the past experiences and observed barriers for implementation of the programs are necessary to trace out. Thus, the present paper highlights the major barriers related to policy, technology, finance and social aspects of already disseminated ICSs based on literature review and questionnaires interview with relevant stakeholders. The statistical analysis of the study is carried out using SPSS statistical tool and presented. Key words: Improved cooking stove (ICS), Stakeholders, and SPSS analyzing tool Journal of the Institute of Engineering, Vol. 7, No. 1, July 2009 pp. 116-120 doi: 10.3126/jie.v7i1.2069